Networks of reciprocation in late antique episcopate. The case of Martin of Tours (Argos, 2025)
In Late Roman Gaul, between the aftermath of Constantine's policies towards the Church and the developments that occurred from the fifth century onwards, stands a gap of at least fifty years during which the bishop’s power began to consolidate its basis. This period has received less attention than the others, although important processes took place within the ecclesiastic structure. This paper will analyze some evidence from the biographical information about Martin of Tours provided by Sulpicius Severus and discuss one aspect of the rise of episcopal power -the exploitation of both vertical and horizontal social relationships.